ANALYSIS OF ELEMENTAL DIFFERENCES IN GREEN SPINACH (AMARANTHUS VIRIDIS) BETWEEN CONVENTIONAL AND HYDROPONIC CULTIVATION METHODS USING LASER-INDUCED BREAKDOWN SPECTROSCOPY (LIBS) METHOD: ANALISIS PERBEDAAN UNSUR DALAM BAYAM HIJAU (AMARANTHUS VIRIDIS) ANTARA METODE BUDIDAYA KONVENSIONAL DAN HIDROPONIK DENGAN MENGGUNAKAN METODE LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Artha Paulina Simamora; Mangasi Alion Marpaung (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to analyze the elemental content in spinach cultivated using conventional and hydroponic methods, utilizing Laser-Induced Breakdown Spectroscopy (LIBS). The research involves collecting spinach leaf samples grown using both cultivation methods. These samples are then processed and analyzed using the LIBS method. In LIBS measurements, appropriate instruments are employed to identify the elements present in the emission spectrum of the samples. The results of this study demonstrate that the LIBS method provides rapid and real-time analysis of the elemental content in spinach. Elements such as Iron (Fe), Magnesium (Mg), Calcium (Ca), Sodium (Na), and Potassium (K) were detected in both tested samples. Although different cultivation methods were employed, there were no significant differences in the types of elements detected. However, the concentration of these elements showed variations.